Secondary battery, battery module, battery pack and power-consuming device
By setting up a glue layer containing carboxylic acid ester polymer and modified styrene-propylene copolymer in the coating area of the negative electrode ear, the problem of short-circuit failure of the secondary battery when the electrode ear is overlapped is solved, and the insulation of the battery is improved and safety performance.
Patent Information
- Application Number
- CN202110902762.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-08-06
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2041-08-06
AI Technical Summary
The safety of secondary batteries is affected by factors such as the structural stability of the positive electrode material, the film forming properties of the negative electrode surface SEI film, the high pressure resistance of the electrolyte, the flame retardant, and the heat resistance of the diaphragm, especially when the electrode is overlapped. A short circuit occurs, causing the battery cell to fail.
The coating area of the negative electrode ear is provided with a glue layer containing carboxylic acid ester polymer, styrene-propylene copolymer and/or modified styrene-propylene copolymer to ensure good compatibility between the glue layer and the negative electrode active material layer and improve insulation and prevents short circuits.
By using the glue layer of modified styrene-propylene copolymer and carboxylic acid ester polymer, the insulation and processing technology of the secondary battery cell are improved, the short-circuit failure ratio during the overlap of the electrodes is reduced, and the battery is improved Safety performance.
Smart Images

Figure CN115706296B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of batteries, and in particular to a secondary battery, a battery module, a battery pack and an electrical device. Background Art
[0002] The safety of secondary batteries is one of the most concerned issues in power batteries. Many factors will affect the safety of secondary batteries, such as the stability of the positive electrode material structure, the film-forming property of the SEI film on the negative electrode surface, the high voltage resistance of the electrolyte, flame retardancy, and heat resistance of the diaphragm. The safety risk of the battery mainly comes from thermal runaway, which is mainly caused by the heat generation rate being much higher than the heat dissipation rate, resulting in a large amount of heat accumulation that cannot be dissipated. Not only does the application of materials determine the safety performance of the battery cell, but during the preparation of the battery, imperfect process preparation may also lead to safety risks of the battery cell, causing internal short circuits and resulting in battery cell fires.
[0003] During the winding process of the battery cell, the positive and negative electrode tabs will fold inward due to process reasons, causing the negative electrode tab to overlap with the positive electrode side or the positive electrode tab to overlap with the negative electrode side, causing the battery cell to short circuit during operation and resulting in serious consequences. Summary of the invention
[0004] The present application is developed in view of the above-mentioned technical problems, and its purpose is to provide a secondary battery that can take into account both high cell safety and good manufacturing processability.
[0005] In order to achieve the above object, the present invention provides a secondary battery, which includes a negative electrode plate, wherein the negative electrode plate includes a negative electrode current collector,
[0006] The negative electrode current collector comprises:
[0007] a negative electrode main body, on the surface of which a negative electrode active material layer is provided; and
[0008] A negative electrode tab, the negative electrode tab comprising a coating area, a glue layer is provided in the coating area,
[0009] The glue layer is adjacent to the negative electrode active material layer, and the glue layer includes a carboxylate polymer, a styrene-acrylic copolymer and / or a modified styrene-acrylic copolymer.
[0010] By setting a glue layer including a carboxylate polymer, a styrene-acrylic copolymer and / or a modified styrene-acrylic copolymer in the coating area of the negative electrode tab, the glue layer is ensured to have good compatibility with the negative electrode active material layer without affecting laser cutting, and the copper foil will not leak out, thereby further improving the insulation. It can be ensured that the battery cell of the secondary battery prepared will not short-circuit even when the tabs are overlapped, thereby reducing the failure rate of the battery cell. At the same time, the glue layer will not have the phenomenon of bulging edges of the diaphragm during the processing, the thermal shrinkage rate of the glue layer is low, and the adhesion between the glue layer and the current collector is also good.
[0011] In some embodiments, in the glue layer, the content of the styrene-acrylic copolymer and / or the modified styrene-acrylic copolymer is 80-90wt% by mass, and optionally 82-86wt%. By setting the content of the styrene-acrylic copolymer and / or the modified styrene-acrylic copolymer in the glue layer to the above range, it can be achieved that the glue layer has good compatibility with the negative electrode active material layer without affecting laser cutting, and the copper foil will not leak out, further improving the insulation, ensuring that the battery cell of the secondary battery prepared does not short-circuit even when the tabs are overlapped, reducing the failure rate of the battery cell, and the glue layer will not have the phenomenon of bulging edge of the diaphragm during processing, further reducing the thermal shrinkage rate of the glue layer, and the adhesiveness of the glue layer and the current collector is also good.
[0012] In some embodiments, the modified styrene-acrylic copolymer is one or more selected from epoxy-modified styrene-acrylic copolymer, organosilicon-modified styrene-acrylic copolymer, organic fluorine-modified styrene-acrylic copolymer and polyolefin-modified styrene-acrylic copolymer, and optionally one or more selected from epoxy-modified styrene-acrylic copolymer and organic fluorine-modified styrene-acrylic copolymer. By using the modified styrene-acrylic copolymer in the adhesive layer, the heat shrinkage rate of the adhesive layer during processing can be further reduced, and the adhesive layer can be better prevented from falling off, thereby further improving the insulation.
[0013] In some embodiments, the crosslinking degree of the styrene-acrylic copolymer and / or the modified styrene-acrylic copolymer is 1% to 3%, and optionally 1.5% to 2.5%.
[0014] In some embodiments, the number average molecular weight of the styrene-acrylic copolymer and / or the modified styrene-acrylic copolymer is 10,000 to 100,000, and optionally 30,000 to 60,000. The number average molecular weight is measured by GPC (gel permeation chromatography).
[0015] By using styrene-acrylic copolymers and / or modified styrene-acrylic copolymers with specific cross-linking degrees and number average molecular weights in the adhesive layer, the viscosity of the adhesive obtained from polycarboxylate polymers and styrene-acrylic copolymers and / or modified styrene-acrylic copolymers can be within an appropriate range, thereby making it easy to apply without generating bubbles during processing, easy to perform laser cutting, reducing the proportion of uncut ears during processing, and further reducing the thermal shrinkage rate of the adhesive layer during processing.
[0016] In some embodiments, the carboxylate polymer is one or more selected from poly(meth)acrylate, polymaleate, and polyvinyl acetate. By using the above carboxylate polymer in the glue layer, a strong hydrogen bond can be formed with the substrate to improve the bonding force; and the low Tg polymer can be formed, which is beneficial to the stability of processing, does not cause the current collector to shrink during the glue coating process, reduces the thermal shrinkage rate of the glue layer during processing, and can improve the processing technology of the glue layer.
[0017] In some embodiments, the carboxylate polymer is one or more selected from poly(meth)acrylates, optionally one or more selected from poly(meth)alkyl acrylates, poly(meth)hydroxyalkyl acrylates or poly(meth)alkenyl acrylates, optionally one or more selected from poly(meth)methyl acrylate, poly(meth)ethyl acrylate, poly(meth)butyl acrylate, poly(meth)isobutyl acrylate, poly(meth)hydroxyethyl acrylate, poly(meth)lauryl acrylate and poly(meth)allyl acrylate. The number average molecular weight of the poly(meth)acrylate can be adjusted and set according to the performance and physical parameters of the required glue layer, such as low Tg, high adhesion, etc. By using the above-mentioned poly(meth)acrylate in the glue layer, the adhesion can be further improved, the heat shrinkage rate of the glue layer during processing can be further reduced, thereby further improving the processing technology of the glue layer, and further improving the laser processing of the negative electrode tab, thereby further reducing the proportion of the tab being cut during processing.
[0018] In some embodiments, the cross-linking degree of the carboxylate polymer is 1% to 3%, and optionally 1.5% to 2.5%.
[0019] In some embodiments, the number average molecular weight of the carboxylate polymer is 100,000 to 200,000, and optionally 140,000 to 180,000. The number average molecular weight is measured by GPC (gel permeation chromatography).
[0020] By using polycarboxylate polymers with a specific degree of cross-linking and number average molecular weight in the adhesive layer, the viscosity of the adhesive obtained from the polycarboxylate polymer and the styrene-acrylic copolymer and / or the modified styrene-acrylic copolymer can be within an appropriate range, so that it is easy to apply without generating bubbles during the processing, and it is easy to perform laser cutting, thereby reducing the proportion of uncut ears during the processing.
[0021] In some embodiments, the adhesive layer also includes a colorant, which may be a colorant with a grayscale value ≤1, or a colorant with a grayscale value ≤0.5. Adding the colorant to the adhesive layer can increase the energy of the laser absorbed by the adhesive layer, which is beneficial for laser cutting and further reduces the proportion of uncut pole ears during processing.
[0022] In some embodiments, the colorant in the adhesive layer is a black pigment, which may be at least one of black masterbatch, carbon black, graphite and lithium iron phosphate. By including the above colorant in the adhesive layer, the energy of the laser absorbed by the adhesive layer can be further increased, thereby improving the laser cutting rate and further reducing the proportion of uncut tabs during processing.
[0023] In some embodiments, the content of the colorant in the adhesive layer is ≤2wt% by mass, and optionally 1-2wt%. By making the content of the colorant in the adhesive layer within the above range, the laser cutting rate can be further improved, and the proportion of uncut tabs during laser processing can be further reduced.
[0024] In some embodiments, the heat shrinkage rate of the adhesive layer at 140° C. is 1% to 2%, and optionally 1.4% to 1.6%. By making the heat shrinkage rate of the adhesive layer within the above range, the adhesive layer can be prevented from peeling off from the substrate, ensuring that the battery cell of the secondary battery prepared does not short-circuit even when the tabs are overlapped, reducing the failure rate of the battery cell, and the adhesive layer and the substrate also have good adhesion.
[0025] In some embodiments, the area ratio of the coating area in the negative electrode tab is 1 / 3 to 2 / 3. When the area ratio of the coating area is within this range, the insulation that can be achieved by the glue coating can be ensured, and the failure rate of the battery cell can be further reduced. At the same time, the tab welding requirements are met, and the tab welding is not interfered with, thereby improving the safety performance of the secondary battery.
[0026] In some embodiments, the adhesive layer further includes ceramic fillers, which may be one or more selected from aluminum oxide, magnesium oxide, calcium oxide, and silicon oxide. By including ceramic fillers in the adhesive layer, the insulation and hardness of the adhesive layer can be further improved, and laser cutting is facilitated, further reducing the proportion of uncut tabs during processing.
[0027] In some embodiments, the content of the ceramic filler in the adhesive layer is ≤5wt% by mass, and optionally 1-4wt%. By making the content of the ceramic filler in the adhesive layer within a specific range, the insulation and hardness of the adhesive layer can be further improved, the laser cutting rate can be further improved, and the proportion of uncut tabs during processing can be further reduced.
[0028] In some embodiments, the particle size of the ceramic filler is 10-100 nm, optionally 20-60 nm. The particle size of the ceramic filler is within the above range, which can ensure the processing performance of the glue coating, avoid missing coating, further reduce the failure rate of the battery cell, and thus further improve the safety performance of the battery.
[0029] A second aspect of the present application provides a battery module, which includes the secondary battery according to the first aspect of the present application.
[0030] A third aspect of the present application provides a battery pack, which includes a battery module according to the second aspect of the present application.
[0031] A fourth aspect of the present application provides an electrical device comprising at least one of the secondary battery according to the first aspect of the present application, the battery module according to the second aspect of the present application, or the battery pack according to the third aspect of the present application.
[0032] The battery module, battery pack and electric device of the present application include the secondary battery provided by the present application, and thus have at least the same advantages as the secondary battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 It is a structural schematic diagram of an embodiment of the negative electrode plate of the present application.
[0034] Figure 2 This is a schematic diagram before cutting the negative electrode tab of this application
[0035] Figure 3 It is a schematic diagram after cutting the negative electrode ear of the present application.
[0036] Figure 4 is a schematic diagram of a secondary battery according to one embodiment of the present application.
[0037] Figure 5 yes Figure 4 An exploded view of a secondary battery according to one embodiment of the present application is shown.
[0038] Figure 6 is a schematic diagram of a battery module according to an embodiment of the present application.
[0039] Figure 7 is a schematic diagram of a battery pack according to one embodiment of the present application.
[0040] Figure 8 yes Figure 7 An exploded view of a battery pack according to one embodiment of the present application is shown.
[0041] Fig. 9 FIG. 1 is a schematic diagram of a device in which a secondary battery according to an embodiment of the present application is used as a power source. DETAILED DESCRIPTION
[0042] In order to make the purpose, technical solution and advantages of the present application clearer, the embodiments of the present application will be described in detail below in conjunction with the accompanying drawings. However, those skilled in the art should understand that these embodiments are only used to illustrate the technical solution of the present application and are not limiting.
[0043] For simplicity, the present application specifically discloses some numerical ranges. However, any lower limit can be combined with any upper limit to form an unclearly recorded range; and any lower limit can be combined with other lower limits to form an unclearly recorded range, and any upper limit can be combined with any other upper limit to form an unclearly recorded range. In addition, although not clearly recorded, each point or single value between the range endpoints is included in the range. In addition, each separately disclosed point or single value itself can be combined with any other point or single value as a lower limit or upper limit or with other lower limits or upper limits to form an unclearly recorded range.
[0044] In the description of this article, it should be noted that, unless otherwise specified, "above" and "below" are inclusive of the number itself, and "several" in "one or several" means two or more.
[0045] The above-mentioned summary of the invention of the present application is not intended to describe each disclosed embodiment or each implementation in the present application. The following description more specifically illustrates exemplary embodiments. In many places throughout the application, guidance is provided by a series of examples, which can be used in various combinations. In each example, enumeration is only used as a representative group and should not be interpreted as exhaustive.
[0046] Secondary battery
[0047] A secondary battery is a battery that can be used continuously by recharging the active materials after the battery is discharged. Usually, a secondary battery includes a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte. During the charge and discharge process of the battery, active ions are embedded and released back and forth between the positive electrode sheet and the negative electrode sheet. The separator is arranged between the positive electrode sheet and the negative electrode sheet, which can insulate electrons and prevent internal short circuits. At the same time, it allows active ions to pass through and move between the positive and negative electrodes, playing an isolating role. The electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet.
[0048] [Negative electrode]
[0049] Figure 1 Schematic diagram of the structure of an embodiment of the negative electrode sheet of the present application. Figure 1 As shown, the negative electrode sheet 100 of the present application includes a negative electrode current collector 30, which includes: a negative electrode main body 301, on the surface of which a negative electrode active material layer 20 is arranged; and a negative electrode tab 302, which includes a coating area, and a glue layer 10 is arranged in the coating area, and the glue layer 10 is adjacent to the negative electrode active material layer 20. The glue layer 10 and the negative electrode tab 302 are located Figure 1In the tab area S shown by the dotted line. The glue layer 10 includes a carboxylate polymer, a styrene-acrylic copolymer and / or a modified styrene-acrylic copolymer. For example, the glue layer 10 may include a carboxylate polymer and a styrene-acrylic copolymer; or, the glue layer 10 may also include a carboxylate polymer and a modified styrene-acrylic copolymer; or, the glue layer 10 may also include a carboxylate polymer, a styrene-acrylic copolymer and a modified styrene-acrylic copolymer. The negative electrode active material layer 20 is disposed on the surface of the negative electrode main body 301 of the negative electrode current collector 30, and the negative electrode current collector 30 without the negative electrode active material layer 20 is a negative electrode tab 302. Figure 1 In the illustrated embodiment, the negative electrode active material layer 20 is disposed on both surfaces of the negative electrode main body 301 of the negative electrode collector 30 , but the present invention is not limited thereto. The negative electrode active material layer 20 may also be disposed on only one surface of the negative electrode main body 301 of the negative electrode collector 30 .
[0050] By providing a glue layer 10 comprising a carboxylate polymer, a styrene-acrylic copolymer and / or a modified styrene-acrylic copolymer in the coating area of the negative electrode tab 302, it is possible to ensure good compatibility between the glue layer 10 and the negative electrode active material layer 20 without affecting laser cutting, and prevent the copper foil from leaking out, thereby further improving the insulation performance. It is possible to ensure that the battery cell made from the negative electrode sheet does not short-circuit even when the tabs are overlapped, thereby reducing the failure rate of the battery cell. At the same time, the glue layer will not have bulging edges on the membrane edge during processing, and the glue layer has a low thermal shrinkage rate, and the glue layer also has good adhesion to the negative electrode current collector.
[0051] In some embodiments, the styrene-acrylic copolymer is a copolymer formed by copolymerizing styrene and acrylic acid. The modified styrene-acrylic copolymer is a copolymer formed by copolymerizing styrene and acrylic acid as the main body and adding one or more modifiers such as epoxy, organosilicon, organic fluorine, polyolefin, etc. The styrene-acrylic copolymer and the modified styrene-acrylic copolymer can be obtained by polymerization methods known in the art, such as emulsion polymerization, solution polymerization, etc. Among them, epoxy, organosilicon, organofluorine, polyolefin and other modifiers can use the commonly used modifiers commonly used in the art for modifying styrene-acrylic copolymers, such as bisphenol A epoxy resin, bisphenol S epoxy resin, bisphenol F epoxy resin, resorcinol diglycidyl ether epoxy resin, tetrahydrophthalic acid diglycidyl ester epoxy resin and other epoxy modifiers; dimethyldichlorosilane, methyltrichlorosilane, phenyltrichlorosilane, diphenyldichlorosilane, methylphenyldichlorosilane and other organosilicon modifiers; polytetrafluoroethylene, polyvinylidene fluoride, polytrifluorochloroethylene and other organofluorine modifiers; styrene-butadiene-polypropylene emulsion, polypropylene and other polyolefin modifiers. In the preparation of styrene-acrylic copolymers or modified styrene-acrylic copolymers, a crosslinking agent can be used, thereby improving the processing technology and hardness of the glue layer. As a crosslinking agent, there is no particular limitation, and crosslinking agents commonly used in the art can be used, for example, diisopropylbenzene peroxide, tert-butyl perbenzoate and the like can be listed. The styrene-acrylic copolymer and the modified styrene-acrylic copolymer may be synthesized products obtained by a conventional polymerization method or commercially available products.
[0052] In some embodiments, the modified styrene-acrylic copolymer in the adhesive layer 10 is one or more selected from epoxy-modified styrene-acrylic copolymers, organosilicon-modified styrene-acrylic copolymers, organic fluorine-modified styrene-acrylic copolymers, and polyolefin-modified styrene-acrylic copolymers, and optionally one or more selected from epoxy-modified styrene-acrylic copolymers and organic fluorine-modified styrene-acrylic copolymers. By using the above-mentioned modified styrene-acrylic copolymers in the adhesive layer, the heat shrinkage rate of the adhesive layer during processing can be further reduced, and the adhesive layer can be better prevented from falling off, thereby further improving the insulation.
[0053] In some embodiments, in the glue layer 10, the content of the styrene-acrylic copolymer and / or the modified styrene-acrylic copolymer is 80-90wt% by mass, and optionally 82-86wt%. By setting the content of the styrene-acrylic copolymer and / or the modified styrene-acrylic copolymer in the glue layer to the above range, it can be achieved that the glue layer has good compatibility with the negative electrode active material layer without affecting laser cutting, and the copper foil will not leak out, and the insulation is further improved. It can be ensured that the battery cell made of the negative electrode pole piece does not short-circuit even when the pole tabs are overlapped, and the failure rate of the battery cell is reduced. At the same time, the glue layer will not have the phenomenon of bulging edge of the membrane during processing, and the thermal shrinkage rate of the glue layer is further reduced. The adhesiveness of the glue layer and the current collector is also good.
[0054] In some embodiments, the crosslinking degree of the styrene-acrylic copolymer and / or the modified styrene-acrylic copolymer is 1% to 3%, optionally 1.5% to 2.5%;
[0055] In some embodiments, the number average molecular weight of the styrene-acrylic copolymer and / or the modified styrene-acrylic copolymer is 10,000 to 100,000, and optionally 30,000 to 60,000. The number average molecular weight is measured by GPC (gel permeation chromatography).
[0056] By using styrene-acrylic copolymers and / or modified styrene-acrylic copolymers with specific cross-linking degrees and number average molecular weights in the adhesive layer 10, the viscosity of the adhesive obtained from the polycarboxylate polymer and the styrene-acrylic copolymer and / or the modified styrene-acrylic copolymer can be within an appropriate range, so that it is easy to apply without generating bubbles during processing, easy to perform laser cutting, and reduce the proportion of uncut ears during processing, and further reduce the thermal shrinkage rate of the adhesive layer during processing.
[0057] In some embodiments, the carboxylate polymer is one or more selected from poly (meth) acrylate, polymaleate, and polyvinyl acetate. By using the above-mentioned carboxylate polymer in the glue layer, a strong hydrogen bond force can be formed with the substrate to improve the bonding force; and the low Tg polymer can be formed, which is beneficial to the stability of processing, will not cause the current collector to shrink during the glue coating process, and reduce the thermal shrinkage rate of the glue layer during processing, which can improve the processing technology of the glue layer. The carboxylates include alkyl carboxylates, alkenyl carboxylates, hydroxyalkyl carboxylates, cycloalkyl carboxylates, aryl carboxylates, etc. Among them, the carbon number of alkyl, alkenyl, and hydroxyalkyl is 1 to 22, optionally 1 to 18, optionally 1 to 12; the carbon number of cycloalkyl is 3 to 12, optionally 3 to 6; the carbon number of aryl is 6 to 22, optionally 6 to 18, optionally 6 to 12.
[0058] In some embodiments, the carboxylate polymer is one or more selected from poly(meth)acrylates, optionally one or more selected from poly(meth)alkyl acrylates, poly(meth)hydroxyalkyl acrylates or poly(meth)alkenyl acrylates, optionally one or more selected from poly(meth)methyl acrylate, poly(meth)ethyl acrylate, poly(meth)butyl acrylate, poly(meth)isobutyl acrylate, poly(meth)hydroxyethyl acrylate, poly(meth)lauryl acrylate and poly(meth)allyl acrylate. By using the above poly(meth)acrylate in the glue layer, the bonding force can be further improved, the heat shrinkage rate of the glue layer during processing can be further reduced, thereby further improving the processing properties of the glue layer, and further improving the laser processing properties of the negative electrode tab, thereby further reducing the proportion of tabs that cannot be cut during processing.
[0059] In some embodiments, the degree of crosslinking of the carboxylate polymer is 1% to 3%, optionally 1.5% to 2.5%;
[0060] In some embodiments, the number average molecular weight of the carboxylate polymer is 100,000 to 200,000, and optionally 140,000 to 180,000. The number average molecular weight is measured by GPC (gel permeation chromatography).
[0061] By using polycarboxylate polymers with a specific degree of crosslinking and number average molecular weight in the adhesive layer, the viscosity of the adhesive obtained from the polycarboxylate polymer and the styrene-acrylic copolymer and / or the modified styrene-acrylic copolymer can be within an appropriate range, so that it is easy to apply without generating bubbles during the processing, and it is easy to perform laser cutting, thereby reducing the proportion of uncut ears during the processing. In addition, the polycarboxylate polymers with a specific degree of crosslinking and number average molecular weight act to suspend the filler while enhancing the adhesion to the current collector.
[0062] The carboxylate polymer can be obtained by polymerizing carboxylate compounds using polymerization methods known in the art, such as free radical polymerization, bulk polymerization, etc. In the preparation of the carboxylate polymer, a crosslinking agent can be used, thereby improving the processability and hardness of the adhesive layer. As the crosslinking agent, there is no particular limitation, and crosslinking agents commonly used in the art can be used, for example, glycerol, diphenylmethane diisocyanate, toluene diisocyanate, etc. can be listed. In addition, the carboxylate polymer can use a synthetic product polymerized by a common polymerization method, or a commercially available product.
[0063] In some embodiments, the glue layer 10 further includes a colorant, which may be a colorant with a gray value of ≤1, or a colorant with a gray value of ≤0.5, or a black pigment, or at least one of black masterbatch, carbon black, graphite, and lithium iron phosphate. By including a colorant in the glue layer, the energy of the laser absorbed by the glue layer can be increased, thereby improving the laser cutting rate and further reducing the proportion of the uncut ear during the processing. The gray value may be measured by using a grayscale scanner.
[0064] In some embodiments, the content of the colorant in the adhesive layer 10 is ≤2wt% by mass, and optionally 1-2wt%. By making the content of the colorant in the adhesive layer within the above range, the laser cutting rate can be further improved, and the proportion of uncut tabs during laser processing can be further reduced.
[0065] In some embodiments, the thermal shrinkage of the adhesive layer 10 at 140° C. is 1% to 2%, and optionally 1.4% to 1.6%. By making the thermal shrinkage of the adhesive layer within the above range, it is possible to prevent the adhesive layer from peeling off from the substrate, ensure that the battery cell made of the negative electrode sheet does not short-circuit even when the tabs are overlapped, reduce the failure rate of the battery cell, and the adhesive layer and the substrate also have good adhesion.
[0066] In some embodiments, the area ratio of the coating area in the negative electrode tab 302 is 1 / 3 to 2 / 3. When the area ratio of the coating area is within this range, the insulation that can be achieved by the glue coating can be guaranteed, and the failure rate of the battery cell can be further reduced. At the same time, the tab welding requirements are met, and the tab welding is not interfered with, thereby improving the safety performance of the secondary battery.
[0067] In some embodiments, the adhesive layer 10 further includes ceramic fillers, which may be one or more selected from aluminum oxide, magnesium oxide, calcium oxide, and silicon oxide. By including ceramic fillers in the adhesive layer, the insulation and hardness of the adhesive layer can be further improved, and laser cutting is facilitated, further reducing the proportion of uncut tabs during processing.
[0068] In some embodiments, the content of the ceramic filler in the adhesive layer 10 is ≤5wt% by mass, and optionally 1-4wt%. By making the content of the ceramic filler in the adhesive layer within a specific range, the insulation and hardness of the adhesive layer can be further improved, the laser cutting rate can be further improved, and the proportion of the uncut tabs during processing can be further reduced.
[0069] In some embodiments, the particle size of the ceramic filler is 10 to 100 nm, optionally 20 to 60 nm. By making the particle size of the ceramic filler within the above range, the processing performance of the glue coating can be guaranteed, and leakage coating can be avoided, and the failure rate of the battery cell can be further reduced, thereby further improving the safety performance of the battery.
[0070] In the negative electrode sheet of the present application, the negative electrode active material layer 20 contains a negative electrode active material. The negative electrode active material can use the negative electrode active material commonly used in the art for preparing the negative electrode of a secondary battery, such as graphite, silicon-based materials, etc. The above-mentioned graphite may include artificial graphite, natural graphite or a mixture thereof. The silicon-based material may be selected from one or more of elemental silicon, silicon oxide compounds (such as silicon monoxide), silicon-carbon composites, silicon-nitrogen composites, and silicon alloys.
[0071] As an example, the negative electrode current collector has two surfaces facing each other in its thickness direction, and the negative electrode active material layer is disposed on either or both of the two facing surfaces of the negative electrode current collector.
[0072] In the negative electrode sheet of the present application, the negative electrode current collector 30 may be a metal foil or a composite current collector. For example, as the metal foil, copper foil may be used. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (such as copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0073] In the negative electrode sheet of the present application, the negative electrode active material layer generally comprises a negative electrode active material and an optional binder, an optional conductive agent and other optional auxiliary agents, and is generally formed by coating and drying a negative electrode slurry. The negative electrode slurry is generally formed by dispersing the negative electrode active material, the optional conductive agent, the optional binder and other optional auxiliary agents in a solvent and stirring them uniformly. The solvent may be N-methylpyrrolidone (NMP) or deionized water.
[0074] As an example, the conductive agent may be selected from one or more of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0075] As an example, the binder can be selected from one or more of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS).
[0076] Other optional auxiliary agents include, for example, thickeners (such as sodium carboxymethyl cellulose (CMC-Na)).
[0077] The negative electrode plate of the present application can be manufactured by a common preparation method. Specifically, the carboxylate polymer, and styrene-acrylic copolymer and / or modified styrene-acrylic copolymer can be dissolved in an aqueous solvent. The aqueous solvent is water and an organic solvent miscible with water, such as alcohols, ketones, esters, etc., and there is no particular limitation. Further, the optional ceramic filler and the optional colorant are dissolved and dispersed in the aqueous solvent in which the carboxylate polymer, styrene-acrylic copolymer and / or modified styrene-acrylic copolymer are dissolved to obtain a glue solution; at the same time, the negative electrode slurry is prepared. Then, as Figure 2 As shown, the glue is applied to the coating area of the negative electrode tab 302 of the negative electrode current collector 20, and the negative electrode slurry is applied to the negative electrode main body 301 of the negative electrode current collector 20, and dried to obtain Figure 2 The negative electrode sheet before the tab cutting is shown. As an example, the glue and negative electrode slurry can be applied at the same time. Then, as shown in FIG. Figure 3 As shown, Figure 2 The negative electrode sheet is cold pressed, and the negative electrode tab 302 is cut by laser, and a plurality of negative electrode tabs 302 are distributed at intervals to obtain Figure 3 The shape of the negative electrode tab 302 is not particularly limited and can be selected as needed.
[0078] [Positive electrode]
[0079] In a secondary battery, a positive electrode sheet generally includes a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector, wherein the positive electrode active material layer includes a positive electrode active material.
[0080] In the secondary battery of the present application, the positive electrode active material layer includes a positive electrode active material. The positive electrode active material may include, but is not limited to, lithium cobalt oxide, lithium nickel manganese cobalt oxide, lithium nickel manganese aluminum oxide, lithium iron phosphate, lithium vanadium phosphate, lithium cobalt phosphate, lithium manganese phosphate, lithium iron silicate, lithium vanadium silicate, lithium cobalt silicate, lithium manganese silicate, spinel lithium manganese oxide, spinel lithium nickel manganese oxide, lithium titanate, etc. The positive electrode active material may use one or more of these.
[0081] The positive electrode active material layer may also optionally include a conductive agent. However, there is no specific limitation on the type of the conductive agent, and those skilled in the art may select the conductive agent according to actual needs. As an example, the conductive agent may be selected from one or more of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.
[0082] In the secondary battery of the present application, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (such as aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0083] The positive electrode sheet of the present application can be prepared according to the common methods in the art. Specifically, a coating can be formed on at least one surface of the current collector by a coating method such as gravure coating, spraying, or hot pressing composite method; the positive electrode active material, conductive agent, and binder are dispersed in a solvent (such as N-methylpyrrolidone (NMP)) to prepare a positive electrode slurry, and the positive electrode slurry is coated on the current collector, and after drying, cold pressing, and other processes, a positive electrode sheet is obtained.
[0084] [Electrolytes]
[0085] The present application embodiment has no specific limitation on the type of electrolyte, and the electrolyte can be selected according to the requirements. For example, the electrolyte can be solid or liquid.
[0086] In some embodiments, the electrolyte is liquid, and generally includes an electrolyte salt and a solvent.
[0087] As an example, the electrolyte salt can be selected from one or more of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalatoborate (LiDFOB), lithium dioxalatoborate (LiBOB), lithium difluorophosphate (LiPO2F2), lithium difluorobis(oxalatophosphate) (LiDFOP) and lithium tetrafluorooxalatophosphate (LiTFOP).
[0088] As an example, the solvent can be selected from one or more of fluoroethylene carbonate (FEC), ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), cyclopentane (SF), dimethyl sulfone (MSM), ethyl methyl sulfone (EMS) and diethyl sulfone (ESE).
[0089] In some embodiments, the electrolyte may also optionally include additives, such as negative electrode film-forming additives, positive electrode film-forming additives, additives for improving battery overcharge performance, additives for improving battery high temperature performance, additives for improving battery low temperature performance, etc.
[0090] [Isolation film]
[0091] The present application embodiment has no particular restrictions on the type of separator, and any known porous separator for secondary batteries can be selected. For example, the separator can be selected from one or more of glass fiber film, non-woven film, polyethylene film, polypropylene film, polyvinylidene fluoride film, and multilayer composite films containing one or more of them.
[0092] In some embodiments, the secondary battery may be a lithium ion secondary battery.
[0093] In some embodiments, the positive electrode sheet, the separator, and the negative electrode sheet may be formed into an electrode assembly by a winding process or a lamination process.
[0094] In some embodiments, the secondary battery may include an outer package, which may be used to encapsulate the electrode assembly and the electrolyte.
[0095] In some embodiments, the outer packaging of the secondary battery can be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the secondary battery can also be a soft package, such as a bag-type soft package. The material of the soft package can be plastic, such as one or more of polypropylene (PP), polybutylene terephthalate (PBT), polybutylene succinate (PBS), etc.
[0096] The embodiment of the present application has no particular limitation on the shape of the secondary battery, which may be cylindrical, square or any other shape. Figure 4 The secondary battery 5 is a square structure as an example.
[0097] In some embodiments, reference Figure 5 , the outer package may include a shell 51 and a cover plate 53. Among them, the shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate are enclosed to form a accommodating cavity. The shell 51 has an opening connected to the accommodating cavity, and the cover plate 53 can be covered on the opening to close the accommodating cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can form an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the accommodating cavity. The electrolyte is infiltrated in the electrode assembly 52. The number of electrode assemblies 52 contained in the secondary battery 5 can be one or more, which can be adjusted according to needs.
[0098] In some embodiments, secondary batteries may be assembled into a battery module. The battery module may contain multiple secondary batteries, and the specific number may be adjusted according to the application and capacity of the battery module.
[0099] Figure 6 3 is an example of a battery module. Figure 6 In the battery module 4, the plurality of secondary batteries 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of secondary batteries 5 may be fixed by fasteners.
[0100] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of secondary batteries 5 are received in the receiving space.
[0101] In some embodiments, the battery modules described above may also be assembled into a battery pack, and the number of battery modules contained in the battery pack may be adjusted according to the application and capacity of the battery pack.
[0102] Figure 7 and Figure 8 1 is a battery pack 1 as an example. Figure 7 and Figure 8 The battery pack 1 may include a battery box and a plurality of battery modules 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3. The upper box body 2 can cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 can be arranged in the battery box in any manner.
[0103] Electrical devices
[0104] Another aspect of the present application provides an electrical device, the electrical device comprising at least one of the negative electrode plate, secondary battery, battery module, or battery pack provided in the present application. The secondary battery can be used as a power source for the device, and can also be used as an energy storage unit for the device. The device can be, but is not limited to, a mobile device (such as a mobile phone, a laptop computer, etc.), an electric vehicle (such as a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck, etc.), an electric train, a ship and a satellite, an energy storage system, etc.
[0105] The device can select a secondary battery, a battery module or a battery pack according to its usage requirements.
[0106] Fig. 9 The device is used as an example. The device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. In order to meet the device's requirements for high power and high energy density of secondary batteries, a battery pack or a battery module can be used.
[0107] Another example of a device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is usually required to be thin and light, and a secondary battery may be used as a power source.
[0108] Example
[0109] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used are conventional products that can be obtained commercially without specifying the manufacturer. The content of each component in the embodiments of the present application, if not otherwise specified, is by mass.
[0110] Example 1
[0111] 1. Preparation of positive electrode sheet:
[0112] The positive electrode active material LiNi 0.6 Co 0.2 Mn 0.2 O2 (NCM622), conductive agent acetylene black, and binder polyvinylidene fluoride (PVDF) are dissolved in solvent N-methylpyrrolidone (NMP) in a weight ratio of 97:2:1, and the mixture is fully stirred and mixed to obtain positive electrode slurry. The positive electrode slurry is evenly coated on the aluminum positive electrode collector, and then dried, cold pressed, and cut to obtain positive electrode sheets.
[0113] 2. Preparation of negative electrode sheet:
[0114] Preparation of negative electrode slurry: artificial graphite as a negative electrode active material, conductive carbon black (Super-P) as a conductive agent, styrene-butadiene rubber (SBR) as a binder, and sodium carboxymethyl cellulose (CMC) as a thickener are mixed in a mass ratio of 97:1:1:1, added into deionized water, and stirred and mixed sufficiently to form a uniform negative electrode slurry to obtain a negative electrode slurry;
[0115] Preparation of glue: 20g polymethyl methacrylate (number average molecular weight: 100,000, cross-linking degree: 1%) and 100g epoxy-modified styrene-acrylic copolymer (number average molecular weight: 10,000, cross-linking degree: 1%) were dissolved in water;
[0116] The negative electrode slurry is coated on the surface of the negative electrode main body of the negative electrode current collector, and the glue is coated on the coating area of the negative electrode tab, and then the negative electrode sheet is obtained through drying, cold pressing, laser cutting and other processes. The area ratio of the glue coating area of the negative electrode tab to the area of the negative electrode tab is 1 / 2.
[0117] 3. Isolation film:
[0118] Polyethylene film is selected as the isolation film.
[0119] 4. Electrolyte:
[0120] Ethylene carbonate (EC), dimethyl carbonate (DMC) and diethyl carbonate (DEC) are mixed at a volume ratio of 1:1:1, and fully dried lithium salt LiPF6 is dissolved in the mixed organic solvent to prepare an electrolyte with a concentration of 1 mol / L.
[0121] 5. Preparation of secondary batteries:
[0122] The preparation methods of Examples 2 to 43 and Comparative Examples 1 to 3 are similar to those of Example 1, except that the relevant preparation parameters of the adhesive layer are changed, as shown in Table 1;
[0123] The negative electrode sheets and secondary batteries prepared in the above-mentioned embodiments and comparative examples were subjected to performance tests by the following methods, and the obtained results are shown in Table 1.
[0124] 1. Determination of compatibility:
[0125] The negative electrode sheets prepared in the above embodiments and comparative examples are placed under the light source of a high-definition microscope, and the area where the glue layer and the active material layer are compatible is observed at a magnification of 100X. If the compatibility is not good, the copper foil will appear golden yellow, and the compatibility is judged by color. Observe 5 different places on the negative electrode sheet with a high-definition microscope. If golden yellow appears in the field of view of any place, it is judged as "×", and if golden yellow does not appear in the entire field of view, it is judged as "○".
[0126] 2. Determination of insulation:
[0127] The negative electrode sheets prepared in the above embodiments and comparative examples were placed on a glass plate, and the positive and negative probes of the insulation resistance meter were placed on the glue layer at a distance of 5 cm to 10 cm. The test was conducted at a DC 220 V for 10 seconds to determine the impedance value.
[0128] 3. Determination of adhesion:
[0129] Two 20 mm × 100 mm test samples were taken from each of the negative electrode sheets prepared in the above embodiments and comparative examples, and adhered to two aluminum plates (100 mm × 25 mm) with double-sided tape, and then the two test samples were bonded with 5 mm × 5 mm double-sided tape. A shear test was performed using a tensile testing machine to test the adhesion.
[0130] 4. Determination of thermal shrinkage:
[0131] Apply the glue liquid on the copper foil, and immediately measure the width W1 of the wet film with a tape measure. Then dry it in an oven at 120°C for 1 hour, and then measure the width W2 of the glue layer after drying. Calculate the thermal shrinkage rate using the formula η=(W1-W2) / W1.
[0132] 5. Laser cutting test of negative electrode sheet:
[0133] 10,000 meters of negative electrode sheets prepared in each embodiment and comparative example were taken and laser cut using a laser die-cutting machine to obtain 5,000 tabs. The uncut ratio of the area of the tab coated with the glue layer during laser cutting was calculated using the following formula.
[0134] Uncut ratio = 1-molded tabs (pcs) / 5000 (pcs)
[0135] 6. Battery short circuit failure ratio test:
[0136] The obtained negative electrode sheet was used to manufacture a battery. The insulation resistance was measured using an insulation resistance meter. When the measured ohmic impedance value was less than 10Ω, it was judged that the battery cell had a short circuit. The number of short-circuited batteries was counted, and the value obtained by dividing the number of short-circuited batteries by the total number of batteries (N=50000) was used as the failure ratio.
[0137] [Table 1]
[0138]
[0139]
[0140] Note:
[0141] A-1: Polymethyl methacrylate (number average molecular weight: 100,000, cross-linking degree: 1%)
[0142] A-2: Polyhydroxyethyl methacrylate (number average molecular weight: 200,000, cross-linking degree: 3%)
[0143] A-3: Polylauryl methacrylate (number average molecular weight: 140,000, cross-linking degree: 1.5%)
[0144] A-4: Polyallyl methacrylate (number average molecular weight: 180,000, crosslinking degree: 2.5%)
[0145] A-5: Polymaleic acid citrate (number average molecular weight: 120,000, cross-linking degree: 1%)
[0146] B-1: Bisphenol A type epoxy modified styrene acrylic copolymer (number average molecular weight: 10,000, crosslinking degree: 1%)
[0147] B-2: dimethyldichlorosilane modified styrene acrylic copolymer (number average molecular weight: 11,000, crosslinking degree: 1.1%)
[0148] B-3: Polytetrafluoroethylene modified styrene acrylic copolymer (number average molecular weight: 12,000, crosslinking degree: 1.1%)
[0149] B-4: Polypropylene modified styrene acrylic copolymer (number average molecular weight: 9,800, crosslinking degree: 0.9%)
[0150] B-5: Styrene-acrylic copolymer (number average molecular weight: 10,000, crosslinking degree: 1%)
[0151] B-6: Bisphenol A type epoxy modified styrene acrylic copolymer (number average molecular weight: 30,000, crosslinking degree: 1.5%)
[0152] B-7: Bisphenol A type epoxy modified styrene acrylic copolymer (number average molecular weight: 60,000, crosslinking degree: 2.5%)
[0153] B-8: Bisphenol A type epoxy modified styrene acrylic copolymer (number average molecular weight: 100,000, crosslinking degree: 3%)
[0154] C-1: Alumina (average particle size: 41 nm)
[0155] C-2: magnesium oxide (average particle size: 44 nm)
[0156] C-3: calcium oxide (average particle size: 42 nm)
[0157] C-4: Silicon dioxide (average particle size: 46 nm)
[0158] D-1: Carbon black
[0159] D-2: Graphite (gray value 0.5)
[0160] D-3: Lithium iron phosphate powder (gray value 1)
[0161] According to the results in Table 1 above,
[0162] In Examples 1 to 18, compared with Comparative Examples 2 to 3, by arranging a glue layer comprising both a carboxylate polymer and a styrene-acrylic copolymer or both a carboxylate polymer and a modified styrene-acrylic copolymer in the coating area of the negative electrode tab, it is possible to ensure that the glue layer has excellent compatibility with the negative electrode active material layer, improve the insulation of the glue layer, improve the adhesion between the glue layer and the current collector, reduce the thermal shrinkage of the glue layer during processing, improve the laser processability of the tab, reduce the proportion of the tab that cannot be cut, and reduce the short-circuit failure proportion of the battery cell, thereby improving safety;
[0163] In addition, by further adding ceramic fillers to the glue layer including the carboxylate polymer and the styrene-acrylic copolymer or the modified styrene-acrylic copolymer, the insulation and hardness of the glue layer can be further improved, and the adhesion between the glue layer and the current collector can be made better;
[0164] Furthermore, by further adding a colorant to the glue layer including the carboxylate polymer and the styrene-acrylic copolymer or the modified styrene-acrylic copolymer, the adhesion between the glue layer and the current collector can be made better, the proportion of the tabs that cannot be cut can be further reduced, and the processing properties of the tabs can be improved.
[0165] Embodiments 44 to 48
[0166] The negative electrode sheet and secondary battery were manufactured in the same manner as in Example 38, except that the area ratio of the glue coating area of the tab in the negative electrode tab was changed to 1 / 2 as shown in Table 2. The short circuit failure ratio of the battery cell was tested in the same manner as above, and the results are shown in Table 2 below.
[0167] [Table 2]
[0168] Coating area ratio Failure rate (%) Embodiment 44 1 / 4 0.03% Embodiment 45 1 / 3 0.01% Embodiment 46 1 / 2 0% Embodiment 47 2 / 3 0.008% Embodiment 48 5 / 6 0.02%
[0169] According to the results in Table 2 above, the failure rate of the battery cell can be further reduced by setting the area ratio of the coating area of the glue layer in the negative electrode tab to 1 / 3 to 2 / 3.
[0170] Embodiments 49 to 55
[0171] A negative electrode sheet and a secondary battery were manufactured in the same manner as in Example 38 except that a filler having a particle size shown in Table 3 was used. The short-circuit failure ratio of the battery cell was tested in the same manner as above, and the results obtained are shown in the following Table 3. In addition, for the obtained negative electrode sheet, the area of the coated region without the coating layer was measured using a vernier caliper, and the value obtained by dividing the area without the coating layer by the total area of the coated region was taken as the non-coating ratio, and the obtained measurement results are shown in Table 3.
[0172] [Table 3]
[0173] Ceramic filler particle size Missing coating ratio (%) Failure rate (%) Embodiment 49 8 0.1% 0.03% Embodiment 50 10 0.05% 0.01% Embodiment 51 20 0% 0% Embodiment 52 40 0% 0% Embodiment 53 60 0% 0% Embodiment 54 100 0.05% 0.01% Embodiment 55 120 0.2% 0.5%
[0174] According to the results in Table 3 above, by further adding ceramic fillers with a particle size within a specific range to the adhesive layer including carboxylic acid ester polymers and styrene acrylic copolymers or carboxylic acid ester polymers and modified styrene acrylic copolymers, the failure rate of the battery cells can be reduced while maintaining the leakage rate within a lower range.
[0175] Those skilled in the art should understand that the above-mentioned embodiments are only some specific embodiments for implementing the present application, and in actual applications, various changes and modifications may be made thereto in form and details, all of which fall within the scope of protection of the present application.
Claims
1. A secondary battery comprising a negative electrode plate, wherein the negative electrode plate comprises a negative electrode current collector, The negative electrode current collector comprises: A negative electrode main body, wherein a negative electrode active material layer is provided on at least one surface of the negative electrode main body; and A negative electrode tab, the negative electrode tab comprising a coating area, a glue layer is provided in the coating area, The glue layer is adjacent to the negative electrode active material layer, and the glue layer includes a carboxylate polymer, a styrene-acrylic copolymer and / or a modified styrene-acrylic copolymer.
2. The secondary battery according to claim 1, wherein: In the adhesive layer, the content of the styrene-acrylic copolymer and / or the modified styrene-acrylic copolymer is 80-90 wt % by mass.
3. The secondary battery according to claim 2, characterized in that: The content of the styrene-acrylic copolymer and / or the modified styrene-acrylic copolymer is 82-86 wt % by mass.
4. The secondary battery according to claim 1 or 2, characterized in that: The modified styrene-acrylic copolymer is one or more selected from epoxy-modified styrene-acrylic copolymer, organosilicon-modified styrene-acrylic copolymer, organofluorine-modified styrene-acrylic copolymer and polyolefin-modified styrene-acrylic copolymer.
5. The secondary battery according to claim 4, characterized in that: The modified styrene-acrylic copolymer is one or more selected from epoxy-modified styrene-acrylic copolymer and organic fluorine-modified styrene-acrylic copolymer.
6. The secondary battery according to claim 1, wherein: The styrene-acrylic copolymer and / or the modified styrene-acrylic copolymer meets at least one of the following conditions: (1) The crosslinking degree of the styrene-acrylic copolymer and / or the modified styrene-acrylic copolymer is 1% to 3%; (2) The number average molecular weight of the styrene-acrylic copolymer and / or the modified styrene-acrylic copolymer is 10,000 to 100,000.
7. The secondary battery according to claim 1, wherein: The styrene-acrylic copolymer and / or the modified styrene-acrylic copolymer meets at least one of the following conditions: The crosslinking degree of the styrene-acrylic copolymer and / or the modified styrene-acrylic copolymer is 1.5% to 2.5%; The number average molecular weight of the styrene-acrylic copolymer and / or the modified styrene-acrylic copolymer is 30,000 to 60,000.
8. The secondary battery according to claim 1, wherein: The carboxylate polymer is one or more selected from poly(meth)acrylate, polymaleate, and polyvinyl acetate.
9. The secondary battery according to claim 8, characterized in that The carboxylate polymer is one or more selected from poly(meth)acrylate.
10. The secondary battery according to claim 9, characterized in that The carboxylate polymer is one or more selected from polyalkyl (meth)acrylate, polyhydroxyalkyl (meth)acrylate or polyalkenyl (meth)acrylate.
11. The secondary battery according to claim 10, characterized in that: The carboxylate polymer is one or more selected from polymethyl (meth)acrylate, polyethyl (meth)acrylate, polyn-butyl (meth)acrylate, polyisobutyl (meth)acrylate, polyhydroxyethyl (meth)acrylate, polylauryl (meth)acrylate and polyallyl (meth)acrylate.
12. The secondary battery according to claim 1, wherein: The carboxylate polymer satisfies at least one of the following conditions: (1) The crosslinking degree of the carboxylate polymer is 1% to 3%; (2) The number average molecular weight of the carboxylate polymer is 100,000 to 200,000.
13. The secondary battery according to claim 12, characterized in that: The carboxylate polymer satisfies at least one of the following conditions: (1) The crosslinking degree of the carboxylate polymer is 1.5% to 2.5%; (2) The number average molecular weight of the carboxylate polymer is 140,000 to 180,000.
14. The secondary battery according to claim 1, wherein: The adhesive layer also includes a colorant, and the grayscale value of the colorant is ≤1.
15. The secondary battery according to claim 14, characterized in that: The gray value of the colorant is ≤0.
5.
16. The secondary battery according to claim 14, wherein: The colorant is a black pigment.
17. The secondary battery according to claim 16, characterized in that: The colorant is at least one of black masterbatch, carbon black, graphite and lithium iron phosphate.
18. The secondary battery according to claim 14, wherein: In the glue layer, the content of the colorant is ≤2wt% by mass.
19. The secondary battery according to claim 18, wherein: In the glue layer, the content of the colorant is 1-2 wt % by mass.
20. The secondary battery according to claim 1, wherein: The thermal shrinkage rate of the adhesive layer at 140° C. is 1% to 2%.
21. The secondary battery according to claim 20, characterized in that: The thermal shrinkage rate of the adhesive layer at 140° C. is 1.4% to 1.6%.
22. The secondary battery according to claim 1, characterized in that: The coating region accounts for 1 / 3 to 2 / 3 of the area of the negative electrode tab.
23. The secondary battery according to claim 1, characterized in that: The adhesive layer also includes ceramic fillers.
24. The secondary battery according to claim 23, characterized in that: The ceramic filler is one or more selected from aluminum oxide, magnesium oxide, calcium oxide and silicon oxide.
25. The secondary battery according to claim 23, characterized in that: In the adhesive layer, the content of the ceramic filler is ≤5wt% by mass.
26. The secondary battery according to claim 25, characterized in that: In the adhesive layer, the content of the ceramic filler is 1 to 4 wt % by mass.
27. The secondary battery according to claim 23, characterized in that: The particle size of the ceramic filler is 10-100 nm.
28. The secondary battery according to claim 27, characterized in that The particle size of the ceramic filler is 20-60 nm.
29. A battery module comprising the secondary battery according to any one of claims 1 to 28.
30. A battery pack comprising the battery module according to claim 29. 31 . An electrical device comprising at least one of the secondary battery according to claim 1 , the battery module according to claim 29 , or the battery pack according to claim 30 .
Citation Information
Patent Citations
Insulating paint containing calcium fluoride, and preparation method, insulating coating, battery pole piece and lithium-ion battery
CN105244456A
Secondary battery current collector and secondary battery using same
CN110098409A